The Significance of Application of Religious Studies Courses at PTKIN in Central Java under Development Dialogue and Preaching - Listiana, Anisa; Na'im, Abdul Haris; Riyadi, Fuad (KALAM, 2023)
This article wants to counter that the study of religions is not intended to make students who study them become apostates, but by studying religions, students are actually more tolerant towards inter-religious communities. This type of research is field research using a phenomenological approach. To obtain data the author used observation, interview and document techniques. This research uses phenomenological analysis. The Problems appear in various forms in this global era is  very complex and multi-dimensional This certainly encourages humanity to return to paying attention to religion in an effort to find solutions to the actual problems faced. The attention seems to have increased significantly, both in the form of ideas, ideas, thoughts and movements. Many people are re-examining and discussing religion as more and more people are increasing their commitment and adherence to religion. Along with that, the field of religious studies is finding its momentum to become the idol of scientists in various fields.